SOLID ORGAN TRANSPLANT CANDIDATES AND RECIPIENTS: DENTISTS' PERSPECTIVE - Birsay Gümrü; Bilge Tarçın (Cumhuriyet University, 2021)
In recent years, dental treatment need in organ transplant candidates and recipients increased in proportion to the increased number of organ transplantations due to advances in immunosuppressive drugs and medical surgical technology. For the transplant candidates and recipients, dental treatment usually requires standard practice procedures that apply to the management of the severely medically compromised patient. However, there are no guidelines, clinical trials or outcome assessments on appropriate dental treatment for these patient groups. Moreover, medicine often forgets dentistry, as there is no consensus among medical transplant specialists as to whether dental infections pose a risk to organ transplant candidates and recipients. The aim of this article is to briefly review the most common oral manifestations in solid organ transplant candidates and recipients, and to suggest a specific dental management protocol to guide medical and dental professionals for general dental management before and after solid organ transplantation.